EFFECTIVENESS OF QARD AL-HASAN FINANCING AS A POVERTY ALLEVIATION MODEL - Widiyanto Widiyanto; Siti Mutamimah; Hendar Hendar (Economic Journal of Emerging Markets, 2011)
Poverty has been proven to be one of the most difficult problems to handle. This research tries to reveal the effectiveness of poverty alleviation model via Qard al-Hasan financing conducted by Baitul Mal Wat Tamwil. It is a model of free-interest financing which financed by zakah, shadaqah and other modes of charity. The result of the study shows that Qardh al-Hasan financing model is effective in empowering the economic activities of the needy. This financing model is supported by the prominent figure in the society and moslem religious leader and the economist. QH financing is potential to be developed further as a poverty alleviation model.Keywords: Qard al-hasan financing, effectiveness, poverty alleviationJEL classification numbers: G19, I39